The media representation of women and HIV/AIDS. How it affects preventative messages - Qakisa, Mpine (Missionalia: Southern African Journal of Mission Studies, 2001)
The media's message about AIDS is skewed. AIDS is portrayed as a disease of ""sinners"" such as prostitutes, homosexuals and people with multiple partners. Popular media continue to carry reports of people who are deliberately infected by sufferers who are seeking revenge. Researchers have also found that the power of any media report is not embedded solely in the individual message but enters a polluted world.
Free